Pancasila Sebagai Sistem Etika, Etika Kehidupan Berbangsa, dan Perlunya Pancasila sebagai Sistem Etika - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Resya Pradita Ummu Syuhada; Restiana Urba Natasyah; Silva Amelia Darrohmah (Lembaga Pengembangan Kinerja Dosen, 2024)
The life of the Indonesian nation and state is guided by Pancasila as an ethical system. Pancasila as the basis of the state functions as a value system that directs people's behavior towards a just, harmonious and dignified life. In the ethical context of national life, Pancasila teaches important values such as tolerance, justice, humanity and unity. These values help build national unity amidst cultural, religious and ethnic diversity. In the current era of globalization, the urgency of Pancasila as an ethical system is increasingly important because the nation's noble values can be damaged by modern issues such as individualism, materialism and social conflict. Indonesian society can use Pancasila as an ethical guideline to develop ways of thinking and acting that are in accordance with the spirit of mutual cooperation, respect for human rights, and a balance between rights and obligations. Pancasila helps society unite and helps people make decisions, both institutionally and personally. Therefore, internalizing Pancasila values as an ethical system is a strategic effort to maintain the nation's immortality in facing the evolution of the times and realizing national ideals for a just, prosperous and prosperous life.